Does Institutional Ownership Moderate the Effect of Transfer Pricing and Sales Growth on Tax Avoidance? - Euis Nessia Fitri; Dani Rahman Hakim (Universitas Negeri Semarang, 2024)
Purposes: This study examines the role of institutional ownership in moderating the effect of transfer pricing and sales growth on corporate tax avoidance of companies in Indonesia's food and beverage sub-sector manufacturing sector. Method: This study selected samples purposively, which resulted in 12 sample companies. We observed the financial reports from each company twice a year from 2015 to 2022, so the total panel data in this study was 192 (12 x 16). Then, this study employs a random effect estimator within a moderation model framework to analyze those data. Findings: This study found that sales growth and institutional ownership increase corporate tax avoidance. However, transfer pricing does not affect corporate tax avoidance. This study uncovers the double-edged sword role of institutional ownership in corporate tax avoidance practices. On the one hand, institutional ownership reduces the effect of transfer pricing on corporate tax avoidance. On the other hand, a company's high institutional ownership could exacerbate corporate tax avoidance caused by increased sales growth. It means that the institutional investor's primary orientation is dividend profits rather than increasing reputation and company value. It urges policymakers to increase the awareness of institutional investors and company managers in the context of corporate tax compliance. Novelty: As far as we know, our study was the first to employ institutional ownership as a moderator variable in the relationship between transfer pricing and sales growth on corporate tax avoidance.